Sistem Informasi Pengolahan Data Lansia Berbasis Web Pada Komunitas Keluarga Angkat Kabupaten Bulukumba - Awaluddin Awaluddin; Husni Sulaiman; Sri Asfirawati Halik (Journal System Information And Computer, 2024)
This research aims to: (1) Designing a Web-based elderly data processing information system in the Bulukumba adoptive family community. (2) Implementing a Web-based elderly data processing information system in the Bulukumba Host Family Community. This research uses the Waterfall research method, where the stages are as follows: (1) Analysis. (2) Design. (3) Coding & Testing. (4) Program Testing. (5) Maintenance. Based on the results of this study it can be concluded that: (1) The Web-Based Elderly Data Processing Information System Information System at the Bulukumba Regency Lift Family Community is designed and built based on problems that occur in the process of managing elderly data, in the design of the elderly data management information system, using uml as a system design which is built using the php programming language using the MySQL database as its database storage and using the waterfall method in the system development stages, testing is carried out using the BlackBox method and based on the tests carried out this system is in accordance with the design. (2) The results of the implementation of the Web-Based Elderly Data Processing Information System at the Bulukumba Regency Lift Family Community, are carried out well in accordance with the design that has been made, including interface implementation, login, data management, This can be seen from the results of testing the use of the system using the System Usability Scale (SUS) obtained a score of 81 from 10 respondents with a letter grade of A and a very good category.